2018
DOI: 10.1111/1365-2664.13073
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting impacts of land‐use change on phylogenetic and functional diversity of tropical forest birds

Abstract: Abstract1. Biodiversity conservation strategies increasingly target maintaining evolutionary history and the resilience of ecosystem function, not just species richness (SR). This has led to the emergence of two metrics commonly proposed as tools for decision making: phylogenetic diversity (PD) and functional diversity (FD). Yet, the extent to which they are interchangeable remains poorly understood.2. We explore shifts in and relationships between FD and PD of bird communities across a disturbance gradient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 51 publications
3
49
0
1
Order By: Relevance
“…To our knowledge, this is the first study on the impact of agricultural intensification on PD of tropical understorey plants. Significant losses in PD with increasing land use intensity were also observed for tropical birds (Chapman, Tobias, Edwards, & Davies, ; Frishkoff et al., ), temperate forest plants (Van Meerbeek et al., ), grasslands (Egorov et al., ), and longleaf pine ecosystems (Turley & Brudvig, ). We can therefore assume that species loss caused by agricultural intensification is generally associated with losses in PD.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, this is the first study on the impact of agricultural intensification on PD of tropical understorey plants. Significant losses in PD with increasing land use intensity were also observed for tropical birds (Chapman, Tobias, Edwards, & Davies, ; Frishkoff et al., ), temperate forest plants (Van Meerbeek et al., ), grasslands (Egorov et al., ), and longleaf pine ecosystems (Turley & Brudvig, ). We can therefore assume that species loss caused by agricultural intensification is generally associated with losses in PD.…”
Section: Discussionmentioning
confidence: 93%
“…Second, behavioural traits split into foraging strata (canopy, mid‐strata, understorey and terrestrial) and foraging mode (trunk/branch, aerial and foliage). Third, following previous studies (Bregman et al, ; Chapman et al, ), we compiled a suite of twelve morphological traits: body mass and length, tarsus length, tail length, wing length, Kipp's distance, hand‐wing index, and bill width, depth, shape and length (both nares to tip and exposed culmen). Measurements of wing length and Kipp's distance—the distance from wing tip to the first (outermost) secondary feather—were not included directly in the matrix but used to calculate hand‐wing index (Kipp's × 100/wing length), a measure of wing aspect ratio correlated with flight efficiency (Pigot, Tobias, & Jetz, ).…”
Section: Methodsmentioning
confidence: 99%
“…Here, functional diversity (FD) quantifies the range of functionally important traits and ecological roles present within a community that are at least partially responsible for sustaining various ecological processes (Leitão et al, ; Petchey & Gaston, ; Tilman, ; Villéger, Mason, & Mouillot, ). Alongside phylogenetic diversity, FD has been proposed to be a key metric of human impacts on biodiversity and ecosystem functioning (Chapman, Tobias, Edwards, & Davies, ; Flynn, Mirotchnick, Jain, Palmer, & Naeem, ), with demonstrated links to the productivity of multiple wild ecosystems (Duffy, Godwin, & Cardinale, ). Evidence also suggests land‐use change can have greater effects on FD than taxonomic diversity (Tinoco, Santillán, & Graham, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the contrasting responses of taxonomic, phylogenetic and functional diversity across environmental conditions such as precipitation and land use gradients (Chapman, Tobias, Edwards, & Davies, ; Meynard et al, ; Monnet et al, ; Seymour, Simmons, Joseph, & Slingsby, ). However, the aforementioned studies have looked at the effect of environmental conditions on biodiversity independently, whereas the interactive effects between two or more environmental conditions on biodiversity remain understudied.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study o f Mediterranean birds showed that taxonomic diversity and funct ional diversity were higher in farmlands than in forests, but forest communities had higher phylogenetic diversity (Morelli, Benedetti , Perna, & Santolini, 2018). Whereas in Borneo, forest sites had hi gher taxonomic, phylogenetic and functional diversity of birds co mpared to oil palm plantations (Chapman et al, 2018). Contrast ing patterns of functional diversity are probably a result of trait selection, as well as usage of different functional diversity metrics (Petchey, Evans, Fishburn, & Gaston, 2007;Villéger, Mason, & Mouillot, 2008).…”
Section: Introductionmentioning
confidence: 99%